Long-Term Results of Primary Reverse Shoulder Arthroplasty for Massive, Irreparable Rotator Cuff Tears Without Glenohumeral Arthritis with a Mean Follow up of 9.4 Years - Dimitrios Varvitsiotis MD, MSc; Stefania Kokkineli MD, MSc; Christopher Feroussis MD, MSc; Nikos Apostolopoulos MD; Dimitrios Zakilas MD; John Feroussis MD, MSc, PhD (Journal of Shoulder and Elbow Arthroplasty, 2023)
Background The aim of this single-center study was to analyze the long-term clinical results of reverse shoulder arthroplasty in patients with massive, irreparable rotator cuff tears without glenohumeral arthritis. Methods A retrospective cohort study of 105 patients (115 shoulders) was conducted. The mean age of the patient group was 76 years (range, 65 to 87 years). The mean clinical follow-up was 9.4 years (range, 5 to 17 years). Pain, range of motion, and complication rates were analyzed pre-operatively and at the last follow-up. Results The mean Constant-Murley score increased from 29 points (range, 21 to 34 points) preoperatively to 68.1 points (range, 57 to 81 points) postoperatively (p<0.05). Scapular notching was present in 50 shoulders (43.5%) and it was grade 1 or 2 in 47 of 115 cases (40.9%) and grade 3 or 4 in 3 of 115 cases (2.6%). Complications occurred in 19 patients (17%). Seven patients (6%) underwent revision surgery. The mean satisfaction rate was 94%. Conclusions Reverse shoulder arthroplasty is a viable treatment for massive, irreparable rotator cuff tears without glenohumeral arthritis with satisfactory clinical outcomes and low complication and reoperation rates with a mean follow up of 9.4 years after surgery.